2017
DOI: 10.1080/09513590.2017.1354366
|View full text |Cite
|
Sign up to set email alerts
|

Randomized crossover study investigating daily versus on-demand vulvar Visnadine spray in women affected by female sexual arousal disorder

Abstract: The aim of the study was to verify the efficacy of vulvar Visnadine spray in premenopausal women affected by female sexual arousal disorder (FSAD). Thirty-eight women aged 25-40 years affected by FSAD were enrolled in the randomized crossover study, by two possible sequences: on-demand, washout, daily (A sequence); and daily, washout, on-demand (B sequence). The Female Sexual Function Index (FSFI) and the Female Sexual Distress Scale (FSDS) were used to assess sexual function and sexual distress, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Both spray and oil produced differences in the FSFI score with respect to placebo [15] [21], although the oil intervention was a pilot study. The other study found results to indicate the efficacy of both daily and on-demand use in women with HSDD [20].…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Both spray and oil produced differences in the FSFI score with respect to placebo [15] [21], although the oil intervention was a pilot study. The other study found results to indicate the efficacy of both daily and on-demand use in women with HSDD [20].…”
Section: Resultsmentioning
confidence: 92%
“…Visasdine is a local treatment applied to the vulvar area 10 min before sexual stimulation. The 3 Visadine interventions are applied in different ways: One of them evaluated the use of spray on demand [15], another evaluated both on demand and daily use, without placebo group [20], whilst a further study assessed the use of Visnadine oil [21]. Both spray and oil produced differences in the FSFI score with respect to placebo [15] [21], although the oil intervention was a pilot study.…”
Section: Resultsmentioning
confidence: 99%
“…Several promising data are also available for visnadine, a principle extracted from the plant Ammi Visnaga, capable of inhibiting smooth muscle contractile responses mediated by calcium entry. A 1% visnadine vulvar spray seems to improve sexual performance in women with arousal disorders [88]. Regarding systemic vasodilators, the evidence is less convincing, with meta-analytic data showing an overall improvement in sexual function compared to that with a placebo, but with some studies have reported negative findings [89].…”
Section: Key Therapeutic Approachesmentioning
confidence: 99%
“…Another new proposal includes the use of Visnadine, an active ingredient of the fruit of Ammi visnaga. The latter demonstrates potent vasodilatory activity and has ameliorated female sexual arousal disorder ( 51 ). Associated a Visnadine, prenylflavonoids, and phytoestrogens have been considered due to their potential role as estrogen receptor alpha selective agonist and may counteract the effects of postmenopausal estrogen loss.…”
Section: Treatmentmentioning
confidence: 99%